THE EFFECT OF AUDITOR EXPERIENCE, OBEDIENCE PRESSURE, AND TASK COMPLEXITY ON AUDIT JUDGMENT : (Empirical Study at a Public Accounting Firm in Surabaya) - Pravitasari, Dyah; Hirmantono, Agung (AGUSPATI Research Institute, 2020)
This study aimed to examine the effect of auditor experience, the pressure of obedience, and the complexity of the task of the audit judgment. Based on the results of the study are expected to provide an overview of the dynamics that occur in a particular public accounting firm audit the auditor in making a judgment. This study was a quantitative research using direct survey through questionnaires. The population in this study is the auditors who work in public accounting firm in Surabaya. Techniques used in sampling is random sampling. Collecting data using questionnaires that have been tested for validity and reliability levels. Data were analyzed using multiple regression analysis, F test, and test T.The results showed that:The auditor's experience, Pressure observance experience, and complexity of the task experience has no effect on audit judgment.